EXAMINING SUBSCRIBER’S LOYALTY IN OMAN’S TELECOM INDUSTRY: A STUDY ON SERVICE QUALITY, TRUST, AND SATISFACTION - Taufiq Hail, Ghilan Al-Madhagy; Almhlawi, Saad Osman Ahmed; Muniyanayaka, Devarajanayaka Kalenahalli; Shakir, Mohanaad; Al-Mamari, Sharifa Suleiman (Bangladesh Journal of Multidisciplinary Scientific Research, 2024)
The Omani telecom industry has evolved significantly, substantially expanding services driven by growing local and global demand. Notable changes have occurred with the entry of new operators, intensifying competition within this dynamic sector. Despite the increasing importance of customer satisfaction and loyalty in Oman’s telecom landscape, limited research has focused on subscribers’ perceptions, which play a crucial role in market competitiveness and economic growth. This study investigates the impact of service quality, trust, and satisfaction on subscribers’ loyalty in Oman’s telecom industry, addressing gaps in understanding customer expectations and needs. Using survey data from 162 active subscribers across Oman’s three primary telecom providers—Omantel, Ooredoo, and Vodafone—this research employed a quantitative approach. It analyzed the data through Partial Least Squares Structural Equation Modeling (PLS-SEM) to explore the impact of service quality, trust, and satisfaction on subscribers’ loyalty toward their preferred telecom providers. The results show that service quality and trust-building on the telecom preferred operator significantly impact customer satisfaction, emphasizing the need for high-quality services and strong customer trust. Furthermore, subscribers’ trust in their provider and satisfaction with its services substantially influence subscriber loyalty, underscoring the critical role of these factors in reducing churn rates in a dynamic and competitive market. This research contributes to understanding subscribers’ behavior in Oman’s telecom landscape. It highlights the crucial role of Quality of service, trust, and customer satisfaction in retaining customer loyalty in a competitive and evolving marketplace. JEL Classification Codes: M10, M31.